A natural promoter variation of SlBBX31 confers enhanced cold tolerance during tomato domestication. Issue 5 (2nd February 2023) - Zhu, Yingfang; Zhu, Guangtao; Xu, Rui; Jiao, Zhixin; Yang, Junwei; Lin, Tao; Wang, Zhen; Huang, Sanwen; Chong, Leelyn; Zhu, Jian‐Kang
Summary: Cold stress affects crop growth and productivity worldwide. Understanding the genetic basis of cold tolerance in germplasms is critical for crop improvement. Plants can coordinate environmental stimuli of light and temperature to regulate cold tolerance. However, it remains unknown which gene in germplasms could have such function. Here, we utilized genome‐wide association study (GWAS) to investigate the cold tolerance of wild and cultivated tomato accessions and discovered that increased cold tolerance is accompanied with tomato domestication. We further identified a 27‐bp InDel in the promoter of the CONSTANS‐like transcription factor (TF) SlBBX31 is significantly linked with cold tolerance. Coincidentally, a key regulator of light signalling, SlHY5, can directly bind to the SlBBX31 promoter to activate SlBBX31 transcription while the 27‐bp InDel can prevent S1HY5 from transactivating SlBBX31 . Parallel to these findings, we observed that the loss of function of SlBBX31 results in impaired tomato cold tolerance. SlBBX31 can also modulate the cold‐induced expression of several ERF TFs including CBF2 and DREBs . Therefore, our study has uncovered that SlBBX31 is possibly selected during tomato domestication for cold tolerance regulation, providing valuable insights for the development of hardy tomato varieties.